Synthesis of Novel Tryptamine Derivatives and Their Biological Activity as Antitumor Agents - Giorgia Simonetti; Carla Boga; Joseph Durante; Gabriele Micheletti; Dario Telese; Paolo Caruana; Andrea Ghelli Luserna di Rorà; Fabio Mantellini; Samantha Bruno; Giovanni Martinelli; Natalia Calonghi (Molecules, 2021)
We synthesized five novel tryptamine derivatives characterized by the presence of an azelayl chain or of a 1,1,1-trichloroethyl group, in turn connected to another heterocyclic scaffold. The combination of tryptamin-, 1,1,1-trichloroethyl- and 2-aminopyrimidinyl- moieties produced compound 9 identified as the most active compound in hematological cancer cell lines (IC50 = 0.57–65.32 μM). Moreover, keeping constant the presence of the tryptaminic scaffold and binding it to the azelayl moiety, the compounds maintain biological activity. Compound 13 is still active against hematological cancer cell lines and shows a selective effect only on HT29 cells (IC50 = 0.006 µM) among solid tumor models. Compound 14 loses activity on all leukemic lines, while showing a high level of toxicity on all solid tumor lines tested (IC50 0.0015–0.469 µM).